Retrospective evaluation of ophthalmological and neurological outcomes for infants born before 24 weeks gestational age in a Swedish cohort. Issue 8 (3rd August 2022) - Hellström, Ann; Jacobson, Lena; Al-Hawasi, Abbas; Hellström-Westas, Lena; Rakow, Alexander; Johnson, Mats; Sävman, Karin; Holmstrom, Gerd; Larsson, Eva; Gränse, Lotta; Saric, Marie; Sunnqvist, Birgitta; et al.
Abstract : Objectives: To retrospectively evaluate ophthalmological and neurological outcomes in a Swedish cohort of infants born before 24 weeks gestational age (GA) and explore risk factors for visual impairment. Setting: Eye and paediatric clinics in Sweden. Participants: Infants screened for retinopathy of prematurity (ROP) (n=399), born before 24 weeks GA, 2007–2018. Cases were excluded if ophthalmological follow-up records could not be traced. Primary and secondary outcome measures: Primary outcomes were ophthalmological, including visual acuity (VA), refractive error, strabismus, nystagmus and cerebral visual impairment (CVI). Secondary outcomes comprised neonatal and neurological morbidities. Data were retrospectively retrieved from medical records. Results: The 355 assessed children had a median GA of 23 weeks and 2 days and a median birth weight of 565 g. At the last available ophthalmological examination, the median age was 4.8 years (range 0.5–13.2 years). Nystagmus was recorded in 21.1%, strabismus in 34.8%, and 51.0% wore spectacles. Seventy-three of 333 (21.9%) were visually impaired, defined as being referred to a low vision clinic and/or having a VA less than 20/60 at 3.5 years of age or older. ROP treatment was a significant risk factor for visual impairment (OR 2.244, p=0.003). Visually impaired children, compared with children without visual impairment, more often had neurological deficits such as intellectual disability 63.8% versus 33.3% (p<0.001), epilepsy 21.1% versus 7.5% (p=0.001) and autism spectrum disorders 32.8% versus 20.9% (p=0.043). Nine of the 355 children had been diagnosed with CVI. Conclusions: Children born before 24 weeks GA frequently had visual impairment in association with neurological deficits. CVI was rarely diagnosed. A multidisciplinary approach for the evaluation and habilitation of these vulnerable infants is warranted. National follow-up guidelines need to be developed and implemented.